2017
DOI: 10.1111/tri.12991
|View full text |Cite
|
Sign up to set email alerts
|

Induction therapy with rabbit antithymocyte globulin versus basiliximab after kidney transplantation: a health economic analysis from a German perspective

Abstract: SUMMARYA health economic analysis was undertaken based on the 1-year database from a randomized study of rabbit anti-human thymocyte immunoglobulin (rATG) versus basiliximab, in kidney transplantation using resource utilization data and cost estimates from three German hospitals. A threestate Markov model was applied to estimate cost-effectiveness to 10 years post-transplant. Total mean treatment cost per patient to year 1 posttransplant was €62 075 vs. €59 767 for rATG versus basiliximab (P < 0.01). rATG ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In KT recipients, recently published economic evaluations of NDI and DI have been favorable, with ATG often being preferred . However, cost‐effectiveness studies of induction in LT remain extremely limited .…”
Section: Discussionmentioning
confidence: 99%
“…In KT recipients, recently published economic evaluations of NDI and DI have been favorable, with ATG often being preferred . However, cost‐effectiveness studies of induction in LT remain extremely limited .…”
Section: Discussionmentioning
confidence: 99%
“…Marfo et al [ 28 ] compared the clinical and economic impact of using short-course versus standard-course ATG, with no significant differences in acute rejection episodes and a significant cost reduction using the short course. Recently, Cremashi et al [ 32 ] compared quality-adjusted life years (QALYs) between ATG and basiliximab, with a modest increase in QALYs and lower long-term costs in the ATG cohort. However, no data on liver transplantation were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews and registry analyses have concluded that with contemporary dosing regimens (total dose ≤6 mg/kg) rATG induction is not associated with an enhanced risk for PTLD or cancer [ 82 84 ]. In terms of expenditure, a recent analysis concluded that rATG or basiliximab induction incurs similar treatment costs over the first two years after kidney transplantation based on data from the high-risk population included in the randomized trial by Brennan et al [ 85 ]. Analyses have not been reported in lower-risk cohorts.…”
Section: Discussionmentioning
confidence: 99%